Safety, Tolerability, and Pharmacokinetics of Single and Multiple Ascending Oral Doses of Youkenafil Hydrochloride, a Phosphodiesterase Type 5 Inhibitor, in Healthy Chinese Male Volunteers. Issue 10 (1st May 2022) - Liang, Beibei; Wang, Jin; Bai, Nan; Chi, Yulong; Wang, Rui; Cai, Yun
Abstract: Youkenafil hydrochloride is a novel selective phosphodiesterase type 5 inhibitor for the treatment of erectile dysfunction. Its safety, tolerability, and pharmacokinetics were evaluated in healthy Chinese male volunteers. In addition, this study explored the effect of food on the pharmacokinetic parameters of youkenafil hydrochloride. The study was divided into 3 trials: a single ascending dose (25, 50, 100, 150, or 200 mg youkenafil), multiple dose (50, 100, or 150 mg youkenafil once daily for 7 consecutive days), and food effect (50 mg youkenafil single dose). The overall tolerability of youkenafil was good. Youkenafil was rapidly absorbed after a single oral dose. Food intake impeded absorption efficiency but had no significant effect on area under the plasma concentration–time curve values. The mean accumulation ratio in area under the plasma concentration–time curve and maximum plasma concentration ranged from 1.3 to 1.6 and from 1.2 to 1.4 after once‐daily dosing. There was no apparent accumulation following consecutive administration for 7 days. Less than 1% of the dose was found in urine as the intact drug for all dose groups. Single‐dose youkenafil up to 200 mg and multiple doses up to 150 mg were generally safe and well tolerated.